Peripartum management of a parturient with type 1C (clearance) von Willebrand disease. (November 2020) - Prior, C.; Sims, K.; Seligman, K.; Jackson, S.; Chau, A.
Highlights: Type 1 von Willebrand disease usually self-corrects in pregnancy. Further workup is warranted if factor levels fail to correct by the third trimester. Type 1C is characterized by decreased plasma von Willebrand factor survival. A diagnosis of type 1C von Willebrand disease has therapeutic implications. Multidisciplinary care including a specialist bleeding disorders team is optimal. Abstract: Peripartum replacement of factor VIII and von Willebrand factor is not usually required in type 1 von Willebrand disease, as the levels of endogenous factors tend to increase to within the normal range as a physiological change of pregnancy. However, there is wide heterogeneity of genotypes and phenotypes associated with type 1 von Willebrand disease. Here, we describe the anesthetic management of a parturient with type 1C von Willebrand disease, a subtype characterized by decreased plasma von Willebrand factor survival.